Tailoring Self-Help Mindfulness and Relaxation Techniques for Stroke Survivors: Examining Preferences, Feasibility and Acceptability - Wang, Xu; Smith, Connie; Ashley, Laura; Hyland, Michael E. (Frontiers in Psychology, 2019)
Objective: Studies on psychological techniques to reduce stroke-related anxiety and/or distress are limited. Even more scarce is research on tailoring such techniques to suit stroke survivors’ needs, especially the needs of those with communication difficulties. To address this gap, we report two sequential studies. Study 1 explored preferred psychological techniques (i.e., mindfulness and relaxation) and ways to modify them for stroke survivors, including those with communication difficulties. Study 2 examined the feasibility and acceptability of these modified techniques with a new sample of survivors. Design: Mixed-methods using qualitative and quantitative approach in both studies. Setting: Community. Participants: All participants were stroke survivors living in the community (study 1: n=13, mean age = 61 years; study 2: n=38, mean age= 65 years) Interventions and procedures: Study 1: seven techniques representing commonly used types of mindfulness and relaxation were filmed on a professionally produced DVD. Participants feedback on how these techniques could be tailored to meet their needs, their preferences for different techniques and reasons for likes and dislikes. Study 2: four favoured techniques from study 1 were modified and re-filmed into a new DVD. A new group of participants were asked to practise them twice daily, five times a week for at least 4 weeks. Results: Four techniques were favoured by participants in study 1. After adaptation, the set of techniques were generally perceived as acceptable, user-friendly and beneficial to participants in study 2. A ‘once a day’ practice frequency could make practising more feasible. Participants also preferred having choices- multiple techniques could be more useful than single technique. Conclusion: Tailoring psychological techniques for stroke survivors is beneficial. The tailored techniques in a self-help DVD format seemed feasible and acceptable for stroke survivors to use, however, a less frequent practice would be easier for survivors.